Experimental aeroacoustic and aerodynamic analysis of a large-scale flap side-edge model - Giraldo, Daniel Acevedo (2019)
The first bypass turbofan engines came into operation in the early 1970s. The need for reductions in the fuel consumption affected aircraft noise positively through reductions in the jet noise. Over the past decades, the bypass ratio of turbofan engines has continuously increased and, as a result, aircraft engine noise has decreased to a level comparable to the noise originated from the turbulent flow around the airframe for take-off and landing conditions. Although aircraft have become quieter, the number of individuals affected by the aviation growth is likely to increase. Airframe noise has been currently identified as the ultimate aircraft noise barrier and many efforts devoted to its reductions have focused specifically on landing gears and high-lift devices, which are the most relevant noise contributors. Some devices have been designed to reduce flap noise, however, not all of them have been successfully tested in a detailed large-scale flap model due to their difficult implementation in real flap side-edges. This research investigates the relationship between the parameters of a large-scale flap model at 1.50×106 Reynolds number and the physics responsible for flap side-edge noise generation, one of the most dominant sources of the airframe noise. Experimental tests were conducted in a wind-tunnel and flow-field measurements were taken by a multi-hole pitot probe and an aerodynamic balance and complemented by phased microphone array techniques towards a deeper understanding of flap side-edge noise sources and their correlations to unsteady vorticity fluctuations. Conventional beamforming and CLEAN-SC and DAMAS deconvolution methodologies provided far-field acoustic spectra estimations and noise source mapping. The model used for the tests consists of an unswept isolated flap element with representative tip details present in conventional medium-range transport aircraft. The instrumentation includes 106 steady pressure taps distributed chord-wise and span-wise and a sand trip tape to transition the laminar boundary layer. Different side-edge devices were assessed towards airframe noise reductions. A perforated side-edge treatment was also applied to the flap side-edge. Results of aerodynamic and aeroacoustic tests conducted in the LAE-1 closed circuit wind tunnel with a closed test section at the São Carlos School of Engineering - University of São Paulo (EESC-USP) at up to 40 m/s flow speeds provided specific information on the aeroacoustic and aerodynamic characterization of the dominant acoustic source mechanisms of the flap model.